The First Human Case of Rickettsia tamurae Infection in Japan - Kaoru Imaoka; Sakae Kaneko; Kenji Tabara; Kenji Kusatake; Eishin Morita (Karger Publishers, 2011)
A case of Rickettsia tamurae infection in Japan is reported. A 76-year-old Japanese male had a tick bite which developed to local skin inflammation on his left leg. Anti-rickettsia antibodies were detected in his serum, and R. tamurae DNA was identified in his blood, the lesional skin, and the tick.